Theological History, Practical Reason, and the Demands of Preaching Today (Homiletic, 2012)
The essay argues that preachers need to study the history of preaching because history is necessary for answering questions raised by renewed consciousness of pluralism. The disestablishment of dominant forms forces historical consciousness upon preachers. In particular, preachers need histories of preaching that hold together theological and empirical perspectives. Preachers need both of what H. Richard Niebuhr called “internal” and “external” histories. There can be no final, speculative resolution of the relationship between theological and empirical perspectives. But Christian preachers can begin to understand the relation between them – and the reason for holding them together – through engagement with the story of the Ascension. Borrowing resources from Michel de Certeau, I argue that the Ascension provides a way of relating theological and empirical perspectives without reducing either to the other.